Behavioral and Immunohistochemical Study of the Effects of Subchronic and Chronic Exposure to Glyphosate in Mice - Ait Bali, Yassine; Ba-Mhamed, Saadia; Bennis, Mohamed (Frontiers in Behavioral Neuroscience, 2017)
Many epidemiological studies have described an adolescent-related psychiatric illness and sensorimotor deficits after Glyphosate based herbicide (GBH) exposure.GBH exposure in animal models of various ages suggests that it may be neurotoxic and could impact brain development and subsequently, behavior in adulthood. However, its neurotoxic effects on adolescent brain remain unclear and the results are limited. The present study was conducted to evaluate the neurobehavioral effects of GBH following acute, subchronic (6 weeks) and chronic (12 weeks) exposure (250 or 500 mg/kg/day) in mice treated from juvenile age until adulthood. Mice were subjected to behavioral testing with the open field, the elevated plus maze, the tail suspension and splash tests.Their behaviors related to exploratory activity, anxiety and depression-like were recorded. After completion of the behavioral testing, adult mice were sacrificed and the expression of tyrosine hydroxylase (TH) in the substantia nigra pars compacta (SNc) and serotonin in the dorsal raphe nucleus (DRN), the basolateral amygdala (BLA) and the ventral medial prefrontal cortex (mPFC) was evaluated using immunohistochemical procedure. Our results indicate that unlike acute exposure, both subchronic and chronic exposure to GBH induced a decrease in body weight gain and locomotor activity, and an increase of anxiety and depression-like behavior levels. In addition, the immunohistochemical findings showed that only the chronic treatment induced a reduction of TH-immunoreactivity. However, both subchronic and chronic exposure produced a reduction of serotonin-immunoreactivity in the DRN, BLA and ventral mPFC. Taken together, our data suggest that exposure to GBH from juvenile age through adulthood in mice leads to neurobehavioral changes that stem from the impairment of neuronal developmental processes.